PENGEMBANGAN STRATEGI BISNIS UNTUK MENINGKATKAN PENERBANGAN KARGO DI BANDARA FATMAWATI SOEKARNO BENGKULU - Candra, Danar Adi; Sundoro, Sundoro; Saputra, Surya Tri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Air cargo plays a vital role in supporting the fast, efficient, and high-value distribution of goods, especially with the rise of e-commerce, export-import activities, and the growth of Indonesias logistics industry. Fatmawati Soekarno Airport in Bengkulu holds significant potential in this sector; however, the market share controlled by Injournay Aviation Services (IAS) remains relatively low despite offering competitive rates. This study aims to analyze the factors behind the low market penetration of IAS, formulate business strategies to enhance its competitiveness, and evaluate effective marketing approaches to attract more potential customers. A qualitative descriptive method with a case study approach was used, involving interviews with service users and airport management, direct observations at the cargo terminal, and supporting documentation. The findings reveal that limited promotion, suboptimal digitalization, and lack of strategic partnerships are key challenges. Recommended strategies include strengthening Business to Customer (B2C) and Business to Business (B2B) approaches, as well as establishing a dedicated business development (sales and marketing) division. This research offers practical insights for airport operators and cargo companies. Future studies are encouraged to explore logistics system digitalization and the impact of multi-stakeholder collaboration on efficiency and air cargo business growth.Keyword: Aviation; Cargo; Business Strategy.Abstrak: Kargo udara memiliki peran penting dalam mendukung distribusi barang secara cepat dan bernilai tinggi, terutama dengan meningkatnya e-commerce, ekspor-impor, dan perkembangan industri logistik di Indonesia. Bandara Fatmawati Soekarno Bengkulu menyimpan potensi besar di sektor ini, namun penguasaan pasar oleh Injournay Aviation Services (IAS) masih rendah meskipun tarifnya kompetitif. Penelitian ini bertujuan menganalisis penyebab rendahnya pangsa pasar IAS, merumuskan strategi peningkatan daya saing, serta mengevaluasi pendekatan pemasaran yang efektif. Metode yang digunakan adalah deskriptif kualitatif dengan pendekatan studi kasus, melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa minimnya promosi, belum optimalnya digitalisasi, serta keterbatasan kerja sama dengan mitra eksternal menjadi kendala utama. Strategi yang direkomendasikan mencakup penguatan pendekatan Business to Customer (B2C), pengembangan Business to Business (B2B), dan pembentukan divisi pengembangan bisnis dalam struktur organisasi. Temuan ini diharapkan menjadi masukan strategis bagi pengelola bandara dan perusahaan kargo. Penelitian lanjutan disarankan untuk menggali potensi digitalisasi sistem logistik dan peran kolaborasi multipihak dalam mendukung efisiensi serta pertumbuhan sektor kargo udara secara berkelanjutan.Kata kunci: Penerbangan; Kargo; Strategi Bisnis.